2010
DOI: 10.1002/ange.201003031
|View full text |Cite
|
Sign up to set email alerts
|

Die Reaktion des weißen Phosphors mit NO+/NO2+[Al(ORF)4]: Bildung von [P4NO]+ durch eine unerwartete Nitrosonium‐Insertion

Abstract: Obwohl seit Jahrzehnten auf dem Gebiet der Polyphosphorchemie intensiv geforscht wird, [1] sind Kenntnisse über homoleptische Polyphosphorkationen immer noch auf die Ergebnisse von massenspektrometrischen [2] und quantenchemischen Untersuchungen [3] beschränkt. Im Allgemeinen sind die kationischen diamagnetischen Käfige mit ungerader Zahl an Phosphoratomen stabiler, wobei P 9 + , das aus zwei C 2v -symmetrischen P 5 -Käfigen mit einem gemeinsamen Phosphoniumatom besteht, eine besondere Stabilität zukommt. [4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 79 publications
1
7
0
2
Order By: Relevance
“…As expected from the calculated frontier orbitals (Supporting Information; Ref. [19]) and the yellow color of the intermediate, the progress of the reaction is facilitated by broad band UV/Vis irradiation that additionally transforms most of the excess P 4 to insoluble red phosphorus, destroys the intermediate [P 4 NO] + , but, according to repeated investigation by NMR spectroscopy, leaves the [P 9 ] + cation intact. Without irradiation we were never able to prepare pure [P 9 ] + by this route.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…As expected from the calculated frontier orbitals (Supporting Information; Ref. [19]) and the yellow color of the intermediate, the progress of the reaction is facilitated by broad band UV/Vis irradiation that additionally transforms most of the excess P 4 to insoluble red phosphorus, destroys the intermediate [P 4 NO] + , but, according to repeated investigation by NMR spectroscopy, leaves the [P 9 ] + cation intact. Without irradiation we were never able to prepare pure [P 9 ] + by this route.…”
mentioning
confidence: 63%
“…phase knowledge and the absence in condensed phases by using the pseudo gasphase conditions provided by the very weakly coordinating [Al(OR F ) 4 ] À anion (R F = C(CF 3 ) 3 ). [17] The optimized synthesis of the first pure phosphorus cation [P 9 ] + [Al(OR F ) 4 ] À proceeds by oxidation of excess P 4 (> 2.5 equivalents) in CH 2 Cl 2 solution with [NO] + [Al-(OR F ) 4 ] À [18] and intermediate formation of the known yellow species [P 4 NO] + [Al(OR F ) 4 ] À [19] according to Figure 1.Previous gas-phase collision-induced dissociation (CID) experiments suggested that the NO moiety is excluded from the [P 4 NO] + cluster as PNO, as [P 3 ] + was formed by direct exclusion of PNO upon collisional activation. With separation of monomeric (SiO 2 -analogous) PNO, the reaction to [P 9 ] + is slightly endergonic according to our conservative estimate.…”
mentioning
confidence: 99%
“…Das Nitrosonium‐Kation [NO]+ schiebt in eine der Tetraederkanten des weißen Phosphors ein und es bildet sich das hochreaktive, neuartige Kation [P4NO]+. Die Synthese lässt sich auch ausgehend von dem einfach zu synthetisierenden Oxidationsmittel NO2[Al(OC(CF3)3)4] und P4 durchführen 1_50…”
Section: Grundlegende Molekülchemie: Phosphor Bis Xenonunclassified
“…Kleinere Kationen mit n = 5 und 7 sollten elektronendefizitäre Wade-Cluster sein, die grçßeren, ab n = 9, dagegen elektronenpräzise Zintl-Systeme mit vierbindigen, formal einfach positiv geladenen Phosphoniumatomen. [19]) und der beobachteten gelben Farbe des Zwischenprodukts lässt sich die Reaktion durch UV/Vis-Bestrahlung positiv beeinflussen: Diese wandelt den überschüssigen weißen Phosphor in unlçslichen roten um, zerstçrt überschüssiges [P 4 NO] + und lässt -wie mit zahlreichen NMR-Experimenten geprüft wurde -das [P 9 ] + -Kation intakt. [17] Die optimierte Synthese des Salzes des ersten reinen Phosphorkations, [P 9 ] + [Al(OR F ) 4 4 ] À [19] (Abbildung 1).…”
unclassified